PENYULUHAN TENTANG JUS SEMANGKA TERHADAP PENURUNAN TEKANAN DARAH DI PUSKESMAS DELI TUA KAB.DELI SERDANG - Adi - Arianto; Rentawati Purba; Sri Sudewi Sitio (INSTITUT KESEHATAN DELI HUSADA, 2021)
Hypertension is a condition where someone experiences an increase in blood pressure above normal 140/90 mm/Hg. Hypertension is often called silent killer because if often doesn’t Have warning signs or symptoms, and many people don’t realize that they have symptoms of hypertension. There is also treatment for hypertension can be done pharmacology and non-pharmacology, among others, with complementary consuming therapy watermelon juice to reduce blood pressure in patients with hypertension. The objective of this study to find out the effect of giving watermelon juice (Citrillus Vulgaris Schardy) to decrease blood pressure in hypertension patient in the KPUM komplex IX village Mekar Sari Deli Tua subdistrict Deli Serdang regency in 2019. This type of research is a pre experiment (pre experimental design) with pre and post in one group ( owe group pretest posttest ). This study uses total sampling where the amount population and sample are the same. Analysis of statistical data used is Uil T pair with the significance level of P 0,05 results and this study, the value P = 0,002. This means there is effect of watermelon juice on reducing blood pressure in patients hypertension it can be concluded that watermelon juice (Citrillus Vulgaris Schard) can effect on changes in blood pressure in patients with hypertension by consuming routinely.